2022
DOI: 10.3390/s22031014
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Based Gas Sensing Material Characterization System for Precise and Simultaneous Measurement of Optical and Electrical Responses

Abstract: Gas sensing performance characterization systems are essential for the research and development of gas sensing materials and devices. Although existing systems are almost completely automatically operated, the accuracies of gas concentration control and of pressure control and the ability to simultaneously detect different sensor signals still require improvement. In this study, a high-precision gas sensing material characterization system is developed based on vacuum technology, with the objective of enabling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Corresponding to the video of the color change of the film when pure H 2 was introduced (Video S2 , Supporting Information), we calculated the color change of the film by applying hydrogen gas for 6 s, which yielded a ΔE ab value of 10.1, which is much larger than 5, the value required to observe a color change with the naked eye (details of the E ab calculations are given in Table S2 , Supporting Information). To further investigate the sensitivity of the film to different hydrogen gas concentrations, we tested the coloring and bleaching abilities of the blue CNT/W/WO 3 /Pd film with seven different hydrogen gas concentrations of 0.1, 0.3, 0.6, 0.9, 1.2, 1.5, and 2% using air as the carrier gas (H 2 /air) at 80 °C (the test setup is shown in Figure S11 , Supporting Information; more details see [ 33 ] ). As shown in Figure 3h , the value of the reflectivity change at a 532‐nm wavelength gradually increased as the hydrogen gas concentration increased, and the maximum ΔR value was 70%.…”
Section: Resultsmentioning
confidence: 99%
“…Corresponding to the video of the color change of the film when pure H 2 was introduced (Video S2 , Supporting Information), we calculated the color change of the film by applying hydrogen gas for 6 s, which yielded a ΔE ab value of 10.1, which is much larger than 5, the value required to observe a color change with the naked eye (details of the E ab calculations are given in Table S2 , Supporting Information). To further investigate the sensitivity of the film to different hydrogen gas concentrations, we tested the coloring and bleaching abilities of the blue CNT/W/WO 3 /Pd film with seven different hydrogen gas concentrations of 0.1, 0.3, 0.6, 0.9, 1.2, 1.5, and 2% using air as the carrier gas (H 2 /air) at 80 °C (the test setup is shown in Figure S11 , Supporting Information; more details see [ 33 ] ). As shown in Figure 3h , the value of the reflectivity change at a 532‐nm wavelength gradually increased as the hydrogen gas concentration increased, and the maximum ΔR value was 70%.…”
Section: Resultsmentioning
confidence: 99%
“…Optical gas sensors are increasingly in demand for various applications such as medical technology, , environmental monitoring, atmospheric sciences, , and industrial process control. Many studies have reported optical gas sensors working based on refractive index change. In the meantime, recent advances in the gas signature at the optical region have revealed that a diverse range of gas molecules exhibit highly characteristic rotational or vibrational transition bands, known as the molecular fingerprint region. , This can pave the path for sensing techniques based on absorption spectroscopy, which is known for its excellent sensitivity, stability, and selectivity . Nevertheless, enabling the simultaneous analysis of multiple target gases in a mixture requires the employment of multiple pairs of band-pass filters and optical detectors in a gas sensor. ,, This approach significantly increases the cost, system complexity, and operating time, especially when dealing with multiple target gases.…”
Section: Introductionmentioning
confidence: 99%